Teachers' conception and classroom practice of assessment for learning - Kurus, Afsah; Khalid, Madihah (Penerbit Universiti Sains Malaysia, 2020)
This article (book Chapter) described the investigation on teachers conception of assessment for learning and their current classroom assessment practices. Three hundred and sixteen primary school teachers who were teaching Year 4 to Year 6 mathematics all over Brunei Darussalam were surveyed through questionnaires, Eight teachers were randomly selected for classroom observation and interview. The survey result showed low implementation of AfL while classroom observation indicated that teachers still practices teacher-centred practices. Interview excerpts revealed that teachers preferred written exercises rather than practical activities in the classroom. It appears that more can be done to integrate AfL into mathematics teaching and learning as desired by the new National Education System for the 21st century.